Productivity, Water Use Efficiency and Economics of Rainfed Niger (Guizotia abyssinica) as Influenced by Mulching and Row Spacing in Red and Lateritic Soil of West Bengal, India - Mandal, Kausik (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted in the red and lateritic loamy sand soil of Birbhum, West Bengal, India during winter season of 2004-05 and 2005-06 to assess the response of rainfed niger [Guizotia abyssinica (L.f.) Cass.] to mulching and row spacing. The results revealed that black polythene mulched plots gave on an average 530 kg ha-1 seed yield that was 5.1, 12.8 and 16.4% higher as compared to rice straw, soil dust and no mulching plots, respectively. Row spacing of 30 cm showed better performance and recorded 6.2% and 11.3% in 2004-05 and 7.1% and 14.6% in 2005-06 higher seed yield as compared to 25 cm and 20 cm row spacing, respectively. Water use efficiency was highest under black polythene mulched treatment and niger crop grown at a row spacing of 30 cm. Highest net return and B:C ratio was recorded under control treatment and niger crop grown at 30 cm row spacing.